PENERAPAN METODE INTEGRAL STIMULATION TERHADAP PASIEN DISLALIA : APPLICATION OF INTEGRAL STIMULATION METHOD TO DYSLALIA PATIENTS - Ekasari, Tetty; Dimalouw, Amanda (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2022)
Dyslalia is an articulation disorder that is not caused by abnormalities in the central nervous system or the anatomy of speech organs. This study aims to determine the success rate of therapy with integral stimulation methods for a 3-year-7-month-old female patient. This research activity was carried out for 2 months in the Bayu Asih District Hospital Purwakarta. The chosen research method is a case study. Initial assessment of the case was carried out by interviewing, observing, testing, and studying documents, and then conducting therapy for 15 meetings which were observed and evaluated. The application of the method of integral stimulation to therapy is carried out to reduce the omission of the consonant /m/ at the word level. In this study, the success rate of therapy was 41.6%. Patients experienced a reduction in the number of omissions in the targeted consonant by 5 points, at the time of the pretest the patient experienced omission in 8 of the 12 test items, and the post-test omission was reduced to 3 test items. Based on the scale designed in this study, the application of the method of integral stimulation was considered quite successful.